Depression, anxiety-like behavior, and memory impairment in mice exposed to chitosan-coated zein nanoparticles - Lima, Vinícius Silva (2019)
The advent of biotechnology provided the synthesis of nanoproducts with diverse applications in the field of medicine, agriculture, food, among others. However, the toxicity of many nanoparticles (NP) currently used, which can penetrate natural systems and impact organisms, is not known. Thus, in this study, we evaluated whether the short exposure (5 days) to low concentrations of chitosan-coated zein nanoparticles (ZNP-CS) (0.2 ng/kg, 40 ng/kg, and 400.00 ng/kg) was capable of causing behavioral alterations compatible with cognitive deficit, as well as anxiety and depression-like behavior in Swiss mice. However, we observed an anxiogenic effect in the animals exposed to the highest ZNP-CS concentration (400.00 ng/kg), without locomotor alterations suggestive of sedation or hyperactivity in the elevated plus maze (EPM) test. We also observed that the ZNP-CS caused depressive-like behavior, indicated by the longer immobile time in the tail suspension test and the animals exposed to ZNP-CS presented deficit in recognition of the new object, not related to locomotor alteration in this test. To the best of our knowledge, this is the first report of the neurotoxicity of ZNP in a mammal animal model, contributing to the biological safety assessment of these nanocomposites.